OVARIAN HAEMODYNAMICS AND FERTILITY IN CATTLE - SATHESHKUMAR, S; RAJA, S (The Indian Journal of Animal Reproduction, 2022)
Ovarian vasculature is an important supportive component that ensures the fertility of an animal. Angiogenesis involves the formation of capillaries from pre-existing microvessels and therefore contributes to vascular remodelling and maturation. This process allows adequate nutritional and hormonal supply for ovarian follicle growth and corpus luteum (CL) formation. Colour-Doppler ultrasound has been used for studying vascular perfusion of ovarian structures and to analyse the blood flow parameters through Doppler spectrum. The ovarian follicle and CL are the major sites of active angiogenesis suggesting that a strong association between normal functionality of these structures and the network of blood vessels. Rapid pulse frequency of the peri-follicular blood flow is a prerequisite factor for induction of ovulation process. Sequential observation during an oestrous cycle revealed progressive increase in luteal blood flow with the increasing endocrine activity. There was an intense increase in luteal blood flow between days 15 – 17 of the oestrous cycle coinciding with the luteolysis. A deficient blood supply to the ovaries could disturb the follicular development, maturation and ovulation leading to various pathological conditions like anoestrus and cystic ovarian degeneration. More clinical research trials are required to develop suitable therapeutic protocols to modulate ovarian vascularity in order to enhance the fertility of cattle.